Evaluating the effectiveness of the PA Foundation's Mental Health Outreach fellowship. Issue 10 (October 2020) - Forbes, Jennifer; Pierce, Caroline; Sappe-Watkins, Lynette
ABSTRACT: Objectives: Mental Health First Aid (MHFA) is designed to help the general public acquire the knowledge and skills needed to respond to a person in a mental health emergency and offer support to someone in emotional distress. Through the PA Foundation's Mental Health Outreach Fellowship, 16 physician assistants (PAs) were selected to become MHFA instructors and teach the course to members of their local communities over 1 year. Methods: MHFA course evaluations, completed by course participants, were reviewed to determine the effectiveness of the PA fellows as instructors. Results: The fellows' mean evaluation instructor presentation score was 4.82 and the mean course content score was 4.75. The national mean for instructor presentation was 4.72 for presentation and 4.66 for course content. The maximum possible score in each category was a 5. Conclusions: The PAs selected for the Mental Health Outreach Fellowship were effective MHFA instructors. Benefits to having a PA serve as the instructor include positively affecting communities by increasing the public's mental health literacy, reducing the stigma associated with mental illness, increasing visibility and promotion of the PA profession, and enhancement of a PA's individual career through education and service.